Comprehensive insights into the response of Alexandrium tamarense to algicidal component secreted by a marine bacterium - Lei, Xueqian; Li, Dong; Li, Yi; Chen, Zhangran; Chen, Yao; Cai, Guanjing; Yang, Xujun; Zheng, Wei; Zheng, Tianling (Frontiers in Microbiology, 2015)
Harmful algal blooms occur throughout the world, threatening human health and destroying marine ecosystems. Alexandrium tamarense is a globally distributed and notoriously toxic dinoflagellate that is responsible for most paralytic shellfish poisoning incidents. The culture supernatant of the marine algicidal bacterium BS02 showed potent algicidal effects on A. tamarense ATGD98-006. In this study, we investigated the effects of this supernatant on A. tamarense at physiological and biochemical levels to elucidate the mechanism involved in the inhibition of algal growth by the supernatant of the strain BS02. Reactive oxygen species (ROS) levels increased following exposure to the BS02 supernatant, indicating that the algal cells had suffered from oxidative damage. The levels of cellular pigments, including chlorophyll a and carotenoids, were significantly decreased, which indicated that the accumulation of ROS destroyed pigment synthesis. The decline of the maximum photochemical quantum yield (Fv/Fm) and relative electron transport rate (rETR) suggested that the photosynthesis systems of algal cells were attacked by the BS02 supernatant. To eliminate the ROS, the activities of antioxidant enzymes, including superoxide dismutase (SOD) and catalase (CAT), increased significantly within a short period of time. Real-time PCR revealed changes in the transcript abundances of two target photosynthesis-related genes (psbA and psbD) and two target respiration-related genes (cob and cox). The transcription of the respiration-related genes was significantly inhibited by the treatments, which indicated that the respiratory system was disturbed. Our results demonstrate that the BS02 supernatant can affect the photosynthesis process and might block the PS II electron transport chain, leading to the production of excessive ROS. The increased ROS can further destroy membrane integrity and pigments, ultimately inducing algal cell death.